2013
DOI: 10.1007/s11103-013-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the GGPP synthase gene family in Arabidopsis thaliana

Abstract: Geranylgeranyl diphosphate (GGPP) is a key precursor of various isoprenoids that have diverse functions in plant metabolism and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
179
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(189 citation statements)
references
References 71 publications
(126 reference statements)
4
179
0
6
Order By: Relevance
“…1) are presumed to produce FPP and GGPP for ubiquinone synthesis. FPPS1L-defective fps1 mutants only showed a limited decrease in UB-9 levels (Closa et al, 2010), suggesting that the biosynthesis of the ubiquinone solanesyl chain might predominantly rely on the supply of GGPP by GGPPS1, the only GGPPS isoform known to be targeted to mitochondria (Beck et al, 2013;Nagel et al, 2015). However, we found that the T-DNA insertion mutant ggpps1-1 (SAIL_559_G01) contains wild-type levels of UB-9 (Supplemental Fig.…”
Section: G11 Activity Is Essential To Produce Both Plastidial Isoprenmentioning
confidence: 87%
See 4 more Smart Citations
“…1) are presumed to produce FPP and GGPP for ubiquinone synthesis. FPPS1L-defective fps1 mutants only showed a limited decrease in UB-9 levels (Closa et al, 2010), suggesting that the biosynthesis of the ubiquinone solanesyl chain might predominantly rely on the supply of GGPP by GGPPS1, the only GGPPS isoform known to be targeted to mitochondria (Beck et al, 2013;Nagel et al, 2015). However, we found that the T-DNA insertion mutant ggpps1-1 (SAIL_559_G01) contains wild-type levels of UB-9 (Supplemental Fig.…”
Section: G11 Activity Is Essential To Produce Both Plastidial Isoprenmentioning
confidence: 87%
“…S4), further indicating that the sG11 protein remains an active GGPPS enzyme. To next determine whether sG11 could also produce GGPP in vivo, we used a heterologous system based on carotenoid (lycopene) production in E. coli strains carrying the pACCRT-BI vector (Beck et al, 2013). Plasmids encoding the full-length G11 or sG11 proteins were used together with pACCRT-BI to cotransform E. coli cells.…”
Section: The Distinct Phenotypes Of G11 Alleles Correlate With Differmentioning
confidence: 99%
See 3 more Smart Citations